Orientasi Perubahan Kurikulum Pendidikan Pesantren - Samsul Bahri (Pascasarjana IAIN Sultan Amai Gorontalo, 2019)
This study orientation changes in the pesantren education curriculum (case study of the Islamic boarding school of the Islamic Boarding School in Kendari. This study uses a field research instrument. The method used is descriptive-analytical with a sociological, historical, comparative approach. Ummushabri Kendari by opening MTS and MA as a modern education system.But the change caused the traditional education system abandoned by students, therefore, traditional pesantren education has lost its function as a pesantren institution, which instead is dominated by the madrasa curriculum and public schools. all pesantren make changes leaving their tradition, this can be seen from the renewal of the Lirboyo pesantren education which succeeded in maintaining the main function of the pesantren institution namely the transmission of Islamic science, the maintenance of Islamic traditions the creation of ulama cadres, and made the Lirboyo pesantren renewal model as a comparison.